Unreal houses : character, gender, and genealogy in the Tale of Genji - Sarra, Edith, 1955- (Harvard East Asian monographs, 2020)
"Argues that, in both form and content, the Tale of Genji re-envisions the elite practice of polygynous marriage and the construction of aristocratic mansions as expressions of familial power. Radically rethinks the Genji by focusing on the figure of the house-encompassing both fictionalized images of mansions and their inhabitants"--